2022
DOI: 10.29228/jrp.117
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and evaluation of the antimicrobial properties of algal alginate; a potential natural protective for cosmetics

Abstract: Sargassum vulgare was sampled by free dives in Iskenderun Bay, Hatay, Turkey, in September 2018.Sargassum vulgare is a material with high economic value because it has compounds that can be used in medical applications such as alginic acid and at the same time it contains carbohydrates and vitamins. Alginates were extracted with a sequential extraction protocol from Sargassum vulgare. Structural characterization of alginate obtained from Sargassum vulgare was determined by FT-IR spectrum, phase structure by XR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Novel research published by Sayin et al [ 46 ] has shown that alginate extracted from Sargassum vulgare can be used as a preservative agent in cosmetics. As the study showed, alginate indicates a higher antimicrobial effect than commercially used herbal preservative 705, which contains glyceryl caprylate and glyceryl undecylenate.…”
Section: Alginate Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Novel research published by Sayin et al [ 46 ] has shown that alginate extracted from Sargassum vulgare can be used as a preservative agent in cosmetics. As the study showed, alginate indicates a higher antimicrobial effect than commercially used herbal preservative 705, which contains glyceryl caprylate and glyceryl undecylenate.…”
Section: Alginate Applicationsmentioning
confidence: 99%
“…The results of the research have shown that alginate from Sargassum vulgare needed less time to initialize antimicrobial activity on microorganisms such as Staphylococcus aureus , Pseudomonas aeruginosa , Candida albicans , Aspergillus brasiliensis , and Escherichia coli. Antimicrobial tests were performed according to the ISO 11930 standard [ 46 ]. The literature provides information about the most proper and the best-quality sources of alginates in cosmetic applications, such as Laminaria hyperborea , Laminaria digitata , and Laminaria japonica , whereas the most common source of marine polysaccharides is brown seaweed in the Phaeophyceae family, Macrocystis pyrifera [ 47 , 48 , 49 ].…”
Section: Alginate Applicationsmentioning
confidence: 99%